2020
DOI: 10.1039/c9mt00253g
|View full text |Cite
|
Sign up to set email alerts
|

Brake dust exposure exacerbates inflammation and transiently compromises phagocytosis in macrophages

Abstract: Working via metal-dependent mechanisms, Fe-rich brake abrasion dust induces inflammatory signalling, disrupts mitochondrial integrity and impairs antimicrobial function in macrophages at a magnitude comparable to that of diesel exhaust particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 74 publications
0
38
0
1
Order By: Relevance
“…Added to this, particle characteristics with respect to both (small) size and (metallic) composition suggest that this currently unregulated source that is concentrated in highly populous urban environments may be a particularly hazardous one. While recent research suggests that the capacity of BAD to harm pulmonary cells is equivalent to that of DEP [39], unambiguous toxicological data are currently lacking. For example, for the most part, toxicological studies of tyre wear have employed pulverized or size-fractionated material, rather than that formed from 'real world' friction between tyres and roadways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Added to this, particle characteristics with respect to both (small) size and (metallic) composition suggest that this currently unregulated source that is concentrated in highly populous urban environments may be a particularly hazardous one. While recent research suggests that the capacity of BAD to harm pulmonary cells is equivalent to that of DEP [39], unambiguous toxicological data are currently lacking. For example, for the most part, toxicological studies of tyre wear have employed pulverized or size-fractionated material, rather than that formed from 'real world' friction between tyres and roadways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this currently unregulated component of traffic emissions is expected to become proportionately more important, as vehicle exhaust PM emissions from road transport are expected to decrease over the coming years. The in vitro study by Selley and co-workers compared the relative toxicity that BAD and DEPs exert on airway macrophages to investigate whether the marked compositional difference between these particle species is reflected in their ability to perturb cell function [39]. Although BAD contained considerably more metals/metalloids than DEP, similar toxicological profiles were observed in U937 monocyte-derived macrophages at minimally cytotoxic doses (4-25 µg ml −1 ; 24 h).…”
Section: (C) the Overall Consensusmentioning
confidence: 99%
“…In our work, suppression of metallothionein expression by DFX or NAC suggests mechanism(s) involving iron and ROS, especially considering the predominance of iron in the UFPM. However, while DFX is often described as an iron-selective chelator, 46 it is nonetheless able to bind ions of multiple other metals, 47,48 albeit with an affinity several orders of magnitude lower than for the DFX-Fe(III) complex. 49 Given that the UFPM that we used also contained other transition metals, these may also be involved, either alone or in concert with iron or other metals.…”
Section: Discussionmentioning
confidence: 99%
“…Small particulate matter is produced from brake pads, tyres, and exhausts, and this is increased when vehicles brake and accelerate, which happens more with speed bumps. Researchers at King’s College London have found that metal particles may cause inflammation and reduce the ability of immune cells to kill bacteria 1. They exposed macrophages to brake dust obtained from a brake testing factory and particulates from diesel exhausts and found that both reduced macrophages’ ability to take up and destroy bacteria.…”
Section: Erm How Do Speed Bumps Affect My Throat?mentioning
confidence: 99%